2006
DOI: 10.1007/s10236-006-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

A model of sand transport in Treporti channel: northern Venice lagoon

Abstract: The origin of the sands in the Venice lagoon has been the subject of an extensive field survey in parallel with numerical modelling. Four transects along Treporti and Burano canals were conducted from which 33 bottom sediment samples were collected. These samples were analysed for grain size and sorting to examine any trends in the granulometry of these sediments that might shed light on transport paths. The modelling study consists of three parts: the sediment transport model SEDTRANS96 was used with a finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This issue has also confirmed by the results of Umgiesser et al (2006), in which a sediment transport model was applied to the Lido inlet. Comparing results from three idealised simulations (tide only, tide with scirocco, tide with bora winds) with a simulation using real forcings over one year, it was found that the long-term results were closest to the simulation when only tidal forcing was taken into account.…”
Section: Hydro-sedimentological Correlationsupporting
confidence: 54%
“…This issue has also confirmed by the results of Umgiesser et al (2006), in which a sediment transport model was applied to the Lido inlet. Comparing results from three idealised simulations (tide only, tide with scirocco, tide with bora winds) with a simulation using real forcings over one year, it was found that the long-term results were closest to the simulation when only tidal forcing was taken into account.…”
Section: Hydro-sedimentological Correlationsupporting
confidence: 54%
“…As a result of their 1-D sediment transport model they concluded that the yearly loss of sand though the Venice inlets is in the order of 0.1 × 10 6 m 3 yr −1 . As well, modelling by Umgiesser et al (2006) indicates an export of sand from the lagoon through Lido inlet through erosion of the major tidal channels.…”
Section: Introductionmentioning
confidence: 85%
“…Lido inlet, in particular, was considered depositional. Defendi et al [88] measured the total transport in the Lido inlet based on calibrated ADCP measurements in 2005-2006 and by coupling the transport model SEDTRANS96 ([89], [90]) to the SHYFEM hydrodynamic model ([91]; [92]), showing a sediment loss of 381 ⋅ 10 3 m 3 /year for the lagoon and of 256 ⋅ 10 3 m 3 /year for the Lido inlet, with a bed-load transport of 29 ⋅ 10 3 m 3 /year. These studies referred to the inlet before the most recent modifications.…”
Section: Discussionmentioning
confidence: 99%